The Influence of Organizational Justice and Perceptions of Organizational Support on Organizational Commitment in PPPK Lecturer Universitas Sembilanbelas November Kolaka - Dwi Ananda Saleeha, Febriyani; Tabara, Reijeng; Astaginy , Niar (Teras Kampus, 2024)
This research aims to determine: (1) The influence of Organizational Justice on Organizational Commitment among PPPK lecturers at Sembilanbelas November University, Kolaka. (2) The influence of perceived organizational support on organizational commitment among PPPK lecturers at Sembilanbelas November University, Kolaka. This research uses a quantitative method approach. Data collection in this research used interviews, literature studies, and distributing questionnaires. The population of this study were all PPPK employees at Sembilanbelas November University, Kolaka, while the sample for this study was 53 people. The data analysis technique used in this research is testing the measurement model (outer model) and testing the structural model (inner model) with Smart PLS 4.0. Based on the research results, it is known that there is a positive and significant influence between the Organizational Justice variables as shown by the P-Value of 0.021. Meanwhile, the variable Perception of organizational support has a positive and significant effect on organizational commitment as indicated by the P-Value value of 0.000